Sonido, imagen y estética (2013)
This report was made with the idea of strengthening the post of youth Nickcity strip. In this use problems were evidenced formats, plus lack of support and commitment from filmmaker as director to form the guidelines for editing each chapter. The work of the VTR Dania Marcela Arboleda Arias Rescue was the use of formats and be very aware that things done before it over time.